Meta-Analisis Kecenderungan Penelitian Skripsi Program Studi Komunikasi dan Penyiaran Islam - Uswatusolihah, Uus; Turhamun, Turhamun (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
This article is a meta-analytic study of the student thesis of the Islamic Communication and Broadcasting Study Program at UIN Prof. KH. Saifuddin Zuhri (UIN Saizu) Purwokerto. This research uses a mix method approach with quantitative and qualitative data collection. The source of quantitative data is the theses of the student of the KPI Study Program UIN Saizu Purwokerto from 2005 to 2021. The thesis data is from printed documents and university digital documents in the form of library repositories. Qualitative data were obtained through interviews with some informants. The analysis technique used is descriptive qualitative, namely combining and generalizing the results of the data in the form of descriptive sentences in detail and as is. The data for each parameter is summed and then a percentage is made. Furthermore, the data is presented in tables and described. The results of this study are in the form of a tendency in choosing research methods, a tendency in choosing a study theme, and the factors that influence research tendencies. The results of this research serve as input and evaluation materials for Study Program KPI managers in formulating research quality development policies and strategies. Practically this research is useful to provide direction for further research.